IMPLEMENTASI TUKAR MENUKAR KAWASAN HUTAN (TMKH) TERKAIT OKUPASI TANAH KAWASAN HUTAN DI KECAMATAN BANTARBOLANG, KABUPATEN PEMALANG, JAWA TENGAH (Studi Kasus: Desa Bantarbolang, Kecamatan Bantarbolang, Kabupaten Pemalang, Jawa Tengah) - Listriani .; Suwanto Adhi; Dzunuwalus Ghulam Manar (Journal of Politic and Government Studies, 2014)
AbstractSwap Forest Area (TMKH) is one of the policy program of the Government as one of themanagement of forest lands to prevent illegal occupation or residence by the community andlocal government. However, the realization of policy implementation Swap Forest Area (TMKH)is experiencing a lot of obstacles. One of these obstacles is the length of the Forest Area Swap(TMKH) is executed, the reason is a change in regulations or new regulations from the centralgovernment as well as technical and administrative procedures are quite complicated. In thisstudy, researchers focused on Bantarbolang Village, District Bantarbolang, Pemalang to see howthe constraints as well as the process and the role of government in implementing Pemalangpolicy implementation Swap Forest Area (TMKH).In this study, researchers used a qualitative method in which the interviews wereconducted, documentation, along with a literature review to obtain information and data andaccurate focus. Interviews were conducted to several stakeholders such as, Head of Legal AffairsPerumPerhutani KPH Agrarian Pemalang, Head of Section Regional Autonomy Developmentand the Office of Land Governance Pemalang, Assistant PerumPerhutani, the village head,district head Bantarbolang, as well as the surrounding communities the District Bantarbolang.From the results of research in the field, that policy Swap Forest Area (TMKH) whichhas been run since 1999 by people experiencing failures due to changes in regulation of thecentral government stating that the Forest Area Swap (TMKH) should be done by the localgovernment, the Regent / Governor or the official level. Pemalang government then took overthe policy process Swap Forest Area (TMKH) which was originally done by the community andreplaced by Local Government. Current policy implementation Swap Forest Area (TMKH) inthe process of beginning to follow the new procedures and regulations, the Minister of ForestryRegulation (Permenhut) No.32 of 2010.In policy implementation Swap Forest Area (TMKH) still requires a lot of evaluation,because of the lack of information and communication related to changes in legislation or newregulations that makes the process of being executed to be blocked. This need for bettercoordination between the parties involved in the implementation, so that communication andinformation can work well.Keywords: Forest Area Swap, Ministerial Regulation No.32 of 2010, Forestry.